A Comprehensive Review of the Clitoris and Its Role in Female Sexual Function. Issue 4 (14th July 2015) - Mazloomdoost, Donna; Pauls, Rachel N.
Abstract Introduction The clitoris is often considered the female version of the penis and less studied compared to its male counterpart. Nonetheless, it carries the same importance in sexual functioning. While it has more recently been allocated the appreciation it deserves, the clitoris should be examined as a separate and unique entity. Aim To review clitoral anatomy, its role in sexual functioning, the controversies of vaginal eroticism and the female prostate, as well as address potential impacts of pelvic surgery on its function. Methods We examined available evidence (from 1950 until 2015) relating to clitoral anatomy, the clitoral role in sexual functioning, vaginal eroticism, female prostate, female genital mutilation/cutting, and surgical implications for the clitoris. Main Outcome Measures Main outcomes included an historical review of the clitoral anatomy and its role in sexual functioning, the controversies regarding vaginal sources of sexual function, and the impact of both reconstructive and nonmedical procedures on the clitoris. Results The intricate neurovasculature and multiplanar design of the clitoris contribute to its role in female sexual pleasure. Debate still remains over the exclusive role of the clitoris in orgasmic functioning. Normal sexual function may remain intact, however, after surgical procedures involving the clitoris and surrounding structures. Conclusions The clitoris is possibly the most critical organ for female sexual health. Its importance is highlighted by the fact that the practice of female genital cutting is often used to attenuate the female sexual response. While its significance may have been overshadowed in reports supporting vaginal eroticism, it remains pivotal to orgasmic functioning of most women. Donna Mazloomdoost and Rachel N. Pauls. A comprehensive review of the clitoris and its role in female sexual function. Sex Med Rev 2015;3:245–263.